2006
DOI: 10.1113/jphysiol.2005.101634
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic γ‐motor output to ankle flexor muscles during locomotion in the decerebrate cat

Abstract: In locomotion, the flexor muscles of the leg are mainly concerned with the relatively constant task of raising the foot, whereas the extensors have the more variable task of support and propulsion at different speeds. This suggests that the way in which the fusimotor system works may differ between the two muscle groups. Observations previously made of the static and dynamic γ-motor firing patterns in the ankle extensor medial gastrocnemius (MG) have therefore been repeated in the flexor tibialis anterior (TA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 35 publications
(58 reference statements)
2
40
0
Order By: Relevance
“…For example, by pulling the foot forward, the force field changed the expected muscle elongation/shortening pattern. This likely changed spindles afferent discharge (Taylor et al 2006). In addition, by pulling the foot up, the force field tended to reduce loading of the experimental leg and to shift body weight to the other leg more rapidly at the end of stance.…”
Section: Initial Exposure To the Force Fieldmentioning
confidence: 99%
“…For example, by pulling the foot forward, the force field changed the expected muscle elongation/shortening pattern. This likely changed spindles afferent discharge (Taylor et al 2006). In addition, by pulling the foot up, the force field tended to reduce loading of the experimental leg and to shift body weight to the other leg more rapidly at the end of stance.…”
Section: Initial Exposure To the Force Fieldmentioning
confidence: 99%
“…These components resemble the dynamic and static ␥-motor firing patterns, respectively, of a fusimotor response (Taylor et al 2006). The onset of the tonic signal, which reflects the position of the eye in the orbit, is masked by the phasic component during a saccade task, making it difficult to determine when area 3a has access to stable eye position information.…”
mentioning
confidence: 99%
“…It was observed that static gamma activity formed a fusimotor template of intended movement (Taylor et al, 2006), and may carry kinematic information of joint angles. In the periphery, direct recording of Ia afferents from the dorsal ganglion cells of decerebrated cats suggested a similar conclusion that Ia afferents carried joint angle information (Stein et al, 2004).…”
Section: Discussionmentioning
confidence: 99%